Gambaran Faktor Yang Mempengaruhi Ibu Dalam Pengambilan Keputusan Pada Persalinan Dukun di Wilayah Puskesmas Rowotengah Kabupaten Jember Tahun 2019 - Maula, Wiwik Daniatul; Aini, Elfira Nurul; Jamhariyah, Jamhariyah (Malang Journal of Midwifery (MAJORY), 2021)
Childbirth is a natural process that occurs in the presence of maternal uterine contractions and followed by cervical opening to remove the baby and placenta. In the area of ??Rowotengah Puskesmas there is still a shaman birth, third (6.92%) in the district of Jember with the number of deaths of 3 mothers in 2018, one of which AKI died because it was assisted by a dukun. The purpose of this study was to determine the description of the factors that influence mothers in making decisions on shaman birth in the Rowotengah Health Center Area. This research is a quantitative study with cross sectional approach. The research instrument is in the form of a questionnaire, with a population of 56 mothers. The sampling technique uses simple random sampling. Data were analyzed univariately. The results of the study of 49 respondents showed that decision making in shaman birth was due to lack of maternal knowledge (59.2%), maternal attitudes in shaman birth decision making were positive (51%), maternal confidence in decision making of shaman birth with positive belief (77.6%), while those who received good support from their husbands in shaman birth decision making were equal to (51%), so that the role of midwives was expected to be more active in providing counseling about the dangers of childbirth as well as increasing cross-sectoral cooperation in midwife and shaman partnership. Keywords: AKI, Attitude, Husband Support, Knowledge, Trust